Non-concentric textured closed surface for huge local field enhancement. (15th December 2016) - Xu, Bingzheng; Li, Zhuo; Liu, Liangliang; Sun, Hengyi; Chen, Chen; Xu, Jia; Yuan, Tao; Gu, Changqing
Abstract: It has been demonstrated that textured closed surfaces are good platforms to support spoof localized surface plasmons with great field confinement and enhancement. Here, we propose a non-concentric textured closed structure to significantly increase the level of field confinement and enhancement. By properly texturing the closed surface with gradient-depth grooves, we show that the incoming electromagnetic waves can be highly confined and focused at the deepest groove on the closed surface. Moreover, we find that the field enhancement factor of this structure is quite sensitive to the polarization angle of the incident wave, which can find potential applications in polarization sensors and energy harvesting devices at microwave and terahertz frequencies.